2012
DOI: 10.1166/jnn.2012.4656
|View full text |Cite
|
Sign up to set email alerts
|

Tin Oxide-Carbon Nanotube Composite for NOX Sensing

Abstract: Tin oxide-single wall carbon nanotube (SWCNT) nano composites are synthesized for gas sensor application. The fabrication includes deposition of porous SWCNTs on thermally oxidized SiO2 substrates followed by rheotaxial growth of Sn and thermal oxidation at 300, 400, 500, and 600 degrees C in air. The effects of oxidation temperature on morphology, microstructure, and gas sensing properties are investigated for process optimization. The tin monoxide oxidized at 400 degrees C showed the highest response at the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 0 publications
2
9
0
Order By: Relevance
“…The average crystalline size of the SnO 2 thin films was approximately 11 nm, as calculated by the Scherrer formula using the (110) peak. This value is smaller than that of previously reported SnO 2 thin films fabricated by rheotaxial growth thermal oxidation [22]. Yamazoe et al [23] studied the H 2 S gas sensing properties of SnO 2 thin films and found that the response to H 2 S abruptly increases for thin films prepared from sol with crystalline sizes larger than 10 nm.…”
Section: Resultsmentioning
confidence: 71%
“…The average crystalline size of the SnO 2 thin films was approximately 11 nm, as calculated by the Scherrer formula using the (110) peak. This value is smaller than that of previously reported SnO 2 thin films fabricated by rheotaxial growth thermal oxidation [22]. Yamazoe et al [23] studied the H 2 S gas sensing properties of SnO 2 thin films and found that the response to H 2 S abruptly increases for thin films prepared from sol with crystalline sizes larger than 10 nm.…”
Section: Resultsmentioning
confidence: 71%
“…The SnO 2 thin films are highly porous as a result of the formation of the nanogranules. The average size of the nanogranules is about 10 nm, which is much smaller compared with that of the SnO 2 thin film fabricated by sputter deposition of Sn film and then thermal oxidation [29]. Herein, the SnO 2 thin film was obtained by reactive sputtering deposition on glass substrate, thus its surface is very smooth as a result of the formation of the ultrafine nanogranules.…”
Section: Resultsmentioning
confidence: 98%
“…The presence of an intermediate phase of SnO peaks in sample ‘b’ is more evident owing to the fact that hydrazine acts as a reducing agent in the sol–gel solution to alleviate the formation of SnO phases. From the XRD analyses one can conclude that the hydrazine‐treated tin‐oxide material contains both phases of SnO and SnO 2 at the same time [16–22]. The formation of SnO seems to be more favourable for the final energy storing devices.…”
Section: Resultsmentioning
confidence: 99%